About the Canonical Meaning of the “Lifelong Office” of the Orthodox Bishops. Is it Unconditional or Conditional? - Nikolchev, Diljan (Forum Theologicum Sardicense, 2025)
The canonical nature of the bishop's lifetime ministry in the local Orthodox Churches has been the subject of intense discussion for several years. Moreover, this issue is becoming increasingly relevant with real-world implications. However, in the Bulgarian Orthodox Church (BOC), it has been overlooked for various reasons. In this context, the present report aims to initiate a scientific-theological discussion on this ecclesiastical-legal issue within our local Church as well.